2018
DOI: 10.1111/aen.12380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest fragmentation on community patterns of social wasps (Hymenoptera: Vespidae) in Central Amazon

Abstract: Landscape fragmentation is one of the greatest threats to environments globally, affecting all living organisms within fragments at many assembly levels. Despite such general assumptions, very few reports exist on the diversity patterns of Amazonian social wasps (Polistinae) in response to fragmentation. Our study aims at addressing how the community patterns of social wasp change from continuous to fragmented landscapes in the Amazon rainforest. We collected social wasps for a year (11 520 trap-hour effort) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Since it presents a larger area, the fragment F4 has a larger availability of hydric and food resources, in addition to a larger number of nesting sites. The abundance of species from the genus Agelaia in diversity studies is a side effect of a large number of individuals in these colonies (Hunt et al, 2001;Graça & Somavilla, 2018), as noted in other studies carried out in the state of Minas Gerais Souza et al, 2015b).…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Since it presents a larger area, the fragment F4 has a larger availability of hydric and food resources, in addition to a larger number of nesting sites. The abundance of species from the genus Agelaia in diversity studies is a side effect of a large number of individuals in these colonies (Hunt et al, 2001;Graça & Somavilla, 2018), as noted in other studies carried out in the state of Minas Gerais Souza et al, 2015b).…”
Section: Resultsmentioning
confidence: 55%
“…This is a consequence of the border effect (Lovejoy et al, 1986), which alters the abiotic and biotic factors (Lovejoy et al, 1986;Wirth et al, 2007); as a result, many species are lost (Woodroffe & Ginsberg, 1998). In the study carried out by Graça and Somavilla (2018) many species were found in both forests, with an emphasis on Agelaia fulvofasciata, Agelaia testacea, Agelaia pallipes, and Polybia rejecta, genera also present in this study. The authors point out that even if the species are present both in the continuous and in the fragmented forest, there was a significant change in the absolute abundance values.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations